Monitoring microcirculation in critical illness. Issue 5 (October 2016) - Kara, Atila; Akin, Sakir; Ince, Can
Abstract : Purpose of review: Critical illness includes a wide range of conditions from sepsis to high-risk surgery. All these diseases are characterized by reduced tissue oxygenation. Macrohemodynamic parameters may be corrected by fluids and/or vasoactive compounds; however, the microcirculation and its tissues may be damaged and remain hypoperfused. An evaluation of microcirculation may enable more physiologically based approaches for understanding the pathogenesis, diagnosis, and treatment of critically ill patients. Recent findings: Microcirculation plays a pivotal role in delivering oxygen to the cells and maintains tissue perfusion. Negative results of several studies, based on conventional hemodynamic resuscitation procedures to achieve organ perfusion and decrease morbidity and mortality following conditions of septic shock and other cardiovascular compromise, have highlighted the need to monitor microcirculation. The loss of hemodynamic coherence between the macrocirculation and microcirculation, wherein improvement of hemodynamic variables of the systemic circulation does not cause a parallel improvement of microcirculatory perfusion and oxygenation of the essential organ systems, may explain why these studies have failed. Summary: Critical illness is usually accompanied by abnormalities in microcirculation and tissue hypoxia. Direct monitoring of sublingual microcirculation using hand-held microscopy may provide a more physiological approach. Evaluating the coherence between macrocirculation and microcirculation in response to therapy seems to be essential in evaluating the efficacy of therapeutic interventions.